Age-related changes of ocular blood flow detecting by laser speckle flowgraphy - N. V. Neroeva; O. V. Zaytseva; T. D. Okhotsimskaya; N. E. Shvetsova; O. I. Markelova (Российский офтальмологический журнал)
Disorders of ocular perfusion are associated with huge amout of diseases, including such socially significant as diabetic retinopathy and glaucoma. To date, there is no gold standard for measuring ocular perfusion. An innovative method for two-dimensional assessment of eye blood flow — laser speckle flowgraphy (LSFG) — has been developed recent years and implemented in ophthalmological practice.Purpose: to evaluate the possibilities of LSFG for determining ocular blood flow and to find out the age dependence of the obtained indicators of ocular blood flow.Materials and methods. The study includes 60 healthy volunteers. The examined persons were divided into 3 groups of 20 people depending on their age — 20–40 years old, 41–60 years old, and over 61 years old. All examined persons had high visual acuity and normal blood pressure. The study was carried out on an LSFG-RetFlow device (Nidek). The shape of the pulse wave, its qualitative and quantitative characteristics including the main parameter of LSFG - MBR (Mean Blur Rate) were determined.Results. A significant decrease with age of most studied parameters of blood flow volume was revealed, the changes were significant (p £ 0.05). The highest MBR parameters were noted in the group of 20–40 years old. In the macular area, MBR values decreased more significantly in the group after 60 years age, while for the optic nerve head (ONH), a decrease has been already noted after 40 years age. In average, the decrease was 25–34 % for the ONH area and 33–38 % for the macular area. Changes of the other parameters of the pulse waveform had a similar trend.Conclusion. LSFG is a reliable method for quantifying ocular blood flow. Our data support that LSFG-derived MBR and pulse wave measurements may be useful biomarkers for ocular perfusion changes. The identified age-related blood flow changes should be taken into account during the analysis of patients data.